Odpowiedzi

Najlepsza Odpowiedź!
2010-02-08T17:30:56+01:00
8z - 2(5z+6)+7z-4 dla z =¾
8z-10z-12+7z-4
5z - 16
5*¾ - 16 = 3,75 - 16 = -12,25

4p-2(8-p²)+5p²-p dla p =½
4p - 16 +2p² + 5p² -p
7p²+3p - 16
7*(½)² + 3*½ - 16 =
=7*0,25 + 1,5 - 16 =
1,75+1,5-16 = -12,75

(x-y)-(x-y) dla x + 0,75,y = - 0,5
(0,75-(-0,5) -(0,75-(-0,5)=
0,75+0,5-0,75-05 = 0
2010-02-08T17:34:42+01:00
8z - 2(5z+6)+7z-4 dla z =¾
=8z-10z-12+7z-4=
= 5z-16=
=5*0,75 - 16 =
= 3,75-16 = -12,25

4p-2(8-p²)+5p²-p dla p =½
=4p-16+2p²+5p²-p=
=3p+7p²-16=
= 3*1/2 + 7*(1/2)² - 16 =
= 1,5+7*1/4 -16=
= 1,5+1,75-16 =
= -12,75


(x-y)-(x-y) dla x + 0,75,y = - 0,5
x-y-x+y = 0
2010-02-08T17:41:12+01:00
8z-2(5z+6)+7z-4=
=8*¾-2*(5*¾+6)+7*¾-4=
=6-2*(3¾+6)+5½-4=
=6-2*9¾+5½-4=
=6-19½+5½-4=
=6-25-4=
=-19-4=-23

4p-2(8-p²)+5p²-p =
=4*½-2*(8-½²)+5*½²-½=
=2-2*(8-¼)+5*¼-½=
=2-2*7¾+1¼-½=
=2-15½+1¼-½=
=2-16¾-½=
=-14¾-½=-15¼

(x-y)-(x-y)=
=[0,75-(-0,5)]-[0,75-(-0,5)]=
=(0,75+0,5)-(0,75+0,5)=
=1,25-1,25=0